Association between MEFV polymorphisms and the susceptibility to ankylosing spondylitis in a Chinese Han population: A case-control study - Song, Jingtao (Medicine (Baltimore), 2018)
The aim of this study was to explore the genetic association of Mediterranean fever (MEFV) gene polymorphisms rs3743930 and rs11466023 with ankylosing spondylitis (AS) susceptibility in a cohort of Chinese Han population. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used for genotyping MEFV polymorphisms in 131 AS patients and 127 healthy controls. Chi-square test was employed to compare the genotype and allele distributions between the case and control groups. Odds ratio (OR) with 95% confidence interval (CI) was calculated to assess the association between MEFV gene polymorphisms and AS incidence. The frequency of the G allele of MEFV polymorphism rs3743930 in the AS group was significantly higher than that in the healthy control group (36.64% vs 28.35%, P < .05). And individuals carrying the GG genotype showed 2.896 folds higher risk of developing AS when compared with CC genotype carriers (OR = 2.896, 95% CI = 1.115–7.519). But no significant differences were detected in either genotype or allele distributions between case and control groups for the polymorphism rs11466023 (P > .05). MEFV gene polymorphism rs3743930 might be significantly associated with AS susceptibility in Chinese Han population, and its G allele might predict high risk of AS.